2022
DOI: 10.3390/plants11192662
|View full text |Cite
|
Sign up to set email alerts
|

Striving for Stability in the Dough Mixing Quality of Spring Wheat under the Influence of Prolonged Heat and Drought

Abstract: The effects of prolonged heat and drought stress and cool growing conditions on dough mixing quality traits of spring wheat (Triticum aestivum L.) were studied in fifty-six genotypes grown in 2017 and 2018 in southern Sweden. The mixing parameters evaluated by mixograph and the gluten protein characteristics studied by size exclusion high-performance liquid chromatography (SE-HPLC) in dough were compared between the two growing seasons which were very different in length, temperature and precipitation. The gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 48 publications
2
7
1
Order By: Relevance
“…A 1°C-3°C rise in mean global air temperature is suggested to decrease wheat production by up to 28% (Shew et al, 2020;Zhang et al, 2022). In fact, in a previous study by our research group on field-grown wheat in Sweden, a yield reduction of up to 40% was observed under combined heat-drought conditions compared with rainy and cold conditions (Lama et al, 2022).…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…A 1°C-3°C rise in mean global air temperature is suggested to decrease wheat production by up to 28% (Shew et al, 2020;Zhang et al, 2022). In fact, in a previous study by our research group on field-grown wheat in Sweden, a yield reduction of up to 40% was observed under combined heat-drought conditions compared with rainy and cold conditions (Lama et al, 2022).…”
Section: Introductionmentioning
confidence: 82%
“…Eight spring wheat genotypes (Diskett, Happy, Bumble, SW1, SW2, SW3, SW4, and SW5) developed in the breeding program at Lantmännen Lantbruk, Svalöv, Sweden, were evaluated. The selected genotypes represented a range in gluten strength, as identified when grown in the field in our previous study (Lama et al, 2022). Diskett, Bumble, and SW3 represented genotypes with unstable gluten strength (>5% variation between years), while Happy, SW1, SW2, SW4, and SW5 represented genotypes with stable gluten strength (<5% variation between years) (Lama et al, 2022).…”
Section: Plant Materialsmentioning
confidence: 99%
See 3 more Smart Citations